Literality of Metaphor in Science Fiction - Muradyan, Gayane (Armenian Folia Anglistika, 2011)
Science fiction is the unity of a real and imaginary narration. The basis of the imaginary is made up of the problems of the contemporary man and society which have found their expression in various uses of the metaphor and in stylistic devices of its literality. The literality of metaphor is a unique stylistic device which can never be found in any other genre of literature, and one would not be mistaken to state that it is the most typical indicator of science fiction.